Guide :High School

Differentiate. (Assume k is a constant.). . y = 1 / (p + ke^p). . I tried using the quotient rule.... (f/g)' = (gf'

Differentiate. (Assume k is a constant.). . y = 1 / (p + ke^p). . I tried using the quotient rule.... (f/g)' = (gf' - fg') / g^2. . and ended up with . (1-pke^(p-1)) / (p+ke^p)^2. . which is apparentl
To simplify things, one could just use differentiation with exponents.y= 1/(p +ke^p)= (p + ke^p)^-1dp/dy = -1 - ke^p ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.

Loading ...

  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.lenny-bruce.com || Terms of Use || Contact || Privacy Policy
Load time: 0.0089 seconds